Advances in library administration and organization. Vol. 19 - Williams, Delmus Eugene; Garten, Edward D. (Emerald, 2002)
This volume addresses an eclectic mix of topics that adapt theoretical concepts relating to the management of libraries to stretch the boundary of practice. The nine contributions include a definition of knowledge management and an outline of a curriculum designed to train knowledge managers developed in Australia, a case study of the application of change management at SMU, and a discussion of how ebooks fit into collection management policies. It also includes two pieces on research on the Internet, one that focuses on student use of this tool and the other on the ethical implications of Internet research. Other contributions include a study of how effective managers work and a discussion of quality assessment in libraries and in American higher education. The volume concludes with discussions of consortia that are developing in Ohio and in Taiwan. While each of these articles are quite different in focus, each deals with an issue that we who are charged with leading libraries must address, and each contributes to the discussions that are likely to clarify our visions of where libraries are going and how we might adapt them to meet the future needs of our clientele. As a result, this volume should take its place beside others in the series as a significant contribution to the literature of management within librarianship.
Includes index.
Keywords: Library administration.; elektronické knihy; electronic books